Nocturia: current concepts and future perspectives. (15th October 2012) - Osman, N. I.; Chapple, C. R.; Wein, A. J.
Abstract Nocturia is a prevalent highly bothersome urinary symptom that may significantly detriment the health and well‐being of sufferers. It is characterized by waking at night to void, each void preceded and followed by sleep, hence leading to fragmentation of sleep and day‐time tiredness. This may result in reduced productivity in the workplace, which contributes to the significant burden to the wider society that nocturia incurs. Nocturia was traditionally viewed as one of the many urinary tract symptoms that occur due to lower urinary tract dysfunction. However, recently it has been recognized that due to its multi‐factorial aetio‐pathogenesis, nocturia should be viewed as distinct clinical condition in its own right. Careful assessment of the nocturic patient is essential so that treatment strategies are guided by the likely causes. Much research is currently being undertaken into the underlying causes and the optimal management approaches. This review will explore the contemporary status of research on nocturia with a focus on the current and newly available pharmacotherapies.